Análise pós-obra de habitações de interesse social visando a identificação de manifestações patológicas - Carraro, Carolina Lemos (2010)
The government housing programs intend to combat the brazilian deficit which is around seven million homes. The quantitative concern, not always meshing with urban and social policies, despite the negative experiences, encourages the production of housing solutions to urban, architectural and constructive repetitive large scale. Faced with this troubling reality, this work seeks, through a case study, contribute to the construction quality of the housing unit of new business aiming to further reduce the environmental impact caused by its premature degradation. The methodology applied feature in theoretical exploratory research. From the knowledge of the programs, processes, management and, finally, any system that involves the housing of social interest, it was proposed to investigate the pathological manifestations in public housing Jardim das Palmeiras , located in Uberlândia-MG. It is a reality site where the construction system and materials used are conventional ones. Analyzing the pathological manifestations identified might be related the possible causes of their occurrence, taking part of the documentation, and thus contribute to the feedback of the process of design, construction management and use of housing of social interest.